The science and business of drug discovery demystifying the jargon - Zanders, Edward D.; SpringerLink (Online service). (Boston, MA Springer US, 2011)
The Science and Business of Drug Discovery is written for those who want to learn about the biopharmaceutical industry and its products whatever their level of technical knowledge. Its aim is to demystify the jargon used in drug development, but in a way that avoids over simplification and the resulting loss of key information. Each of the nineteen chapters is illustrated with figures and tables which clarify some of the more technical points being made. Also included is a drug discovery case history which draws the relevant material together into a single chapter. In recognizing that it is difficult to navigate through the many external resources dealing with drug development, the book has been written to guide the reader towards the most appropriate information sources, including those listed in the two appendices. The following topics are covered: Different types of drugs: from small molecules to stem cells Background to chemistry of small and large molecules Historical background to drug discovery, pharmacology and biotechnology The drug discovery pipeline: from target discovery to marketed medicine Commercial aspects of drug discovery Challenges to the biopharmaceutical industry and its responses Material of specific interest to technology transfer executives, recruiters and pharmaceutical translators About the Author Dr. Edward D. Zanders has over twenty years? experience as a scientist and research manager in both a major pharmaceutical company and in smaller biotechnology organizations. He has been responsible for a number of drug discovery programs for diseases such as asthma and rheumatoid arthritis and has been involved in research management at a senior level. He has also published extensively on subjects ranging from biochemistry and immunology to computer-aided drug design; more recently he has written about the application of online networking to drug discovery. In 2004 he founded PharmaGuide Ltd, a training and consultancy company that delivers courses on the drug discovery industry to various professional groups including technology transfer executives, recruiters and technical translators. It is through delivering these courses that he has been able to develop his own way of conveying complex information about drug discovery to non scientists, while at the same time being able to communicate with PhD level scientists at their level of expertise.
Introduction -- Introduction to Drugs and Drug Targets -- Background to Chemistry of Small and Large Molecules -- Laying the Foundations: Drug Discovery from Antiquity to the Twenty-First Century -- Drug Discovery Pipeline Overview -- Target Discovery -- Medicinal Chemistry -- Biotherapeutics -- Screening for Hits -- Process Chemistry and Formulation -- Preclinical Development -- Clinical Trials -- Regulatory Affairs and Marketing Approval -- Diagnostics and Personalized Medicine -- Putting it All Together: A Drug Development Case History -- Commercial Aspects of Drug Development -- Challenges and Responses -- Technology Transfer Executives -- Recruitment Executives -- Pharmaceutical Translators and Interpreters.
Electronic reproduction.
Keywords: Drug development--Terminology.; Pharmaceutical industry--Terminology.; Drug Discovery